2004
DOI: 10.1093/njaf/21.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Bat Activity in Harvested and Intact Forest Stands in the Allegheny Mountains

Abstract: We used Anabat acoustical monitoring devices to examine bat activity in intact canopy forests, complex canopy forests with gaps, forests subjected to diameter-limit harvests, recent deferment harvests, clearcuts and unmanaged forested riparian areas in the Allegheny Mountains of West Virginia in the summer of 1999. We detected eight species of bats, including the endangered Indiana bat (Myotis sodalis). Most bat activity was concentrated in forested riparian areas. Among upland habitats, activity of silver-hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 22 publications
12
47
0
Order By: Relevance
“…In contrast to the Myotis group, Lasionycteris noctivagans were negatively related to canopy cover, clutter 9–12 m, and small and medium tree densities. This is consistent with our prediction and results from preceding studies that suggest large‐bodied species are more often associated with open stands, particularly between the shrub layer and tree‐limb canopy (Patriquin & Barclay 2003; Owen et al 2004). L. noctivagans activity had a positive relationship with clutter at 0–6‐m heights, but dense vegetation at lower heights may not directly affect larger‐bodied bats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to the Myotis group, Lasionycteris noctivagans were negatively related to canopy cover, clutter 9–12 m, and small and medium tree densities. This is consistent with our prediction and results from preceding studies that suggest large‐bodied species are more often associated with open stands, particularly between the shrub layer and tree‐limb canopy (Patriquin & Barclay 2003; Owen et al 2004). L. noctivagans activity had a positive relationship with clutter at 0–6‐m heights, but dense vegetation at lower heights may not directly affect larger‐bodied bats.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, forest management may have profound effects on bat use because it can alter structural complexity by generating edges and openings, by reducing clutter for foraging bats, or by potentially limiting or increasing available roost sites (Grindal & Brigham 1999). Previous studies have focused on the influence of various forest management strategies on bat activity in rural landscapes (e.g., Grindal & Brigham 1998; Grindal & Brigham 1999; Swystun et al 2001; Menzel et al 2002; Owen et al 2004), but information for urban forests is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Rodhouse et al ., ), these designs are difficult to implement over a large area and often need to be balanced with low probability of detection of many bat species in certain habitat types within heterogeneous landscapes (Johnson et al ., ; Coleman, ). Accordingly, to maximize detection of multiple species in our study area, we prioritized selection of study sites within or near (<100 m) riparian areas based on: (1) findings from previous studies suggesting summer bat activity is generally positively correlated with riparian habitat (Vaughan et al ., ; Ford et al ., ; Menzel et al ., ; Rogers et al ., ) and (2) placement of acoustical devices in riparian areas has been shown to maximize detection probabilities for a variety of bat species present within Fort Drum (Owen et al ., ; Menzel et al ., ). Thus, our placement of acoustical detectors within riparian areas was strategically based on the availability of open habitat near water sources where bat foraging activity and probability of detection would be maximized.…”
Section: Methodsmentioning
confidence: 99%
“…We downloaded, identified and tallied the number of species identifications per hour for each site on each sample night (see Ford et al ., for specific echolocation pass identification methodologies). The resulting echolocation tallies commonly are used as an index of bat activity that in turn serves as a surrogate for bat relative abundance (Hayes, ; Law & Chidel, ; Gehrt & Chelsvig, ; Owen et al ., ). Such activity indices fail to account for error associated with variation in species‐specific differences in detection probabilities (MacKenzie et al ., ); however, by standardizing methods across years and controlling for sampling conditions (as herein), indices still can provide inference to trends in population dynamics over time (Link & Sauer, ).…”
Section: Methodsmentioning
confidence: 99%
“…Yet little is known regarding the effects of wildfire on bat species [9], [16], [17]. Existing knowledge of bat response to forest disturbance is largely from studies of ecological thinning [18], various levels of harvest [19], [20], [21], [22], [23], or prescribed burning [24], [25], [26]. Such studies have shown that activity of bats increases following disturbance, with increased activity attributed to three possible causes.…”
Section: Introductionmentioning
confidence: 99%